Comparison of Different Chemical and Mechanical Modalities for Implant Surface Decontamination: Activity against Biofilm and Influence on Cellular Regrowth—An In Vitro Study - Citterio, Filippo; Zanotto, Elisa; Pellegrini, Gaia; Annaratore, Laura; Barbui, Anna Maria; Dellavia, Claudia; Baima, Giacomo; Romano, Federica; Aimetti, Mario (Frontiers in Surgery, 2022)
Objectives – The aim of this in vitro study was to compare the efficacy of chemical and mechanical methods for decontamination of titanium dental implant surfaces previously infected with polymicrobial biofilms in a model simulating a peri-implant defect. Furthermore, the effect of each decontamination protocol on MG-63 osteoblast-like cells morphology and adhesion to the treated implants was assessed. Background – Peri-implantitis is a growing issue in dentistry and evidence about implant surface decontamination procedures is lacking and inconclusive. Methods - A total of 40 previously biofilm-contaminated implants were placed into a custom-made model simulating a peri-implant defect and randomly assigned to 5 treatment groups: C) control (no treatment); AW) air-abrasion without any powder; ESC) air-abrasion with powder of erythritol, amorphous silica and 0.3% chlorhexidine; HBX) decontamination with a sulfonic/sulfuric acid solution in gel; and HBX+ESC) a combination of HBX and ESC. Microbiological analysis was performed on 5 implants per treatment group and the residual viable bacterial load measured in log10CFU was counted for each bacterial strain and for the total number of colonies. The remaining 3 implants per group and 3 non-contaminated implants (NC) were used to assess surface biocompatibility using scanning electron microscope and backscattered electron microscope after seeding with MG-63 cells. Results – A significant decontaminant effect was achieved using HBX or HBX+ESC while no differences were shown among other groups. The percentage of implant surface covered by adherent MG-63 cells was influenced by the treatment method. Progressive increases of covered surface were observed through groups C, AW, ESC, HBX, HBX+ESC, and NC. Conclusions – Combination of mechanical and chemical decontamination may provide more predictable results than mechanical cleaning alone.